PROFESSIONAL ACCOUNTING PRACTICE TODAY AND TOMORROW. - Perry, Donald P. (The Accounting Review, 1944)
Abstract Many problems arising as the result of wartime conditions will continue to perplex for years after the war. Uncertainties which will be resolved only by future developments have in the past presented difficulties in accounting practice and have been a basis for criticism by some who hold the erroneous conception that accounting statements are by their nature intended to be exact and accurate representations of fact. Industries expect after the war a more or less protracted period of retooling, plant reconversion and rehabilitation and redevelopment of markets. In conclusion, a brief word should be said as to the general bearing these thoughts may have on accounting education. The educator is always confronted with the question of where the emphasis in curriculum and instruction should be placed as between teaching accounting techniques and development of understanding of principles, policies and underlying social sciences. Obviously, the man trained to recognize the significance of new situations and to meet them on the basis of an experienced judgment and a command of basic principles has been a more useful member of the profession in wartime than the narrowly-trained technician. This is likely to be true also in years to come.